Craneofacial manifestaciones in patients with renal osteodystrophy - Yuritza Yoleinnis Hernández Arenas; Cristian Andres Puello Correa; Francisco Levi Duque Serna; Jose Vicente Vallejo Ochoa (Editorial Ciencias Médicas, 2022)
Introduction: Renal osteodystrophy is a diffuse metabolic osteopathy, related to chronic renal failure, which includes various pathologies in the musculoskeletal system. It occurs in response to metabolic disorders generated by electrolyte changes, chronic inflammation and hormonal alteration. These variations modify the process of bone remodeling. Clinical manifestations include alteration in the parenchyma and bone stroma, and range from expansive lesions, producing deformity, to pathological fractures of the bone. Objective: Relate the clinical, imaging and histological manifestations in the skull-facial bone component for the diagnosis of renal osteodystrophy. Case Presentation: Two clinical cases of patients with chronic kidney disease and secondary underlying hyperparathyroidism are presented, with multiple masses in the jaws that cause facial asymmetry and functional alteration. Tomographic images reveal alteration in cortical and trabecular bone morphology. Both individuals showed alterations in levels of parathyroid hormone, alkaline phosphatase, phosphorus and serum calcium. Histopathology verified fibro-bone tissue with neoformed bone and great vascularization, with multinucleated osteoclast-like cells without the presence of hemosiderin. Patients were attended in an interdisciplinary way between internal medicine, endocrinology and maxillofacial surgery. Conclusions: Patients with advanced chronic kidney disease present alteration of the structure and bone and mineral metabolism. Such a situation can compromise the craniofacial bone complex. Severe cases of renal osteodystrophy are characterized by a marked expansion of the jaws, which generates asymmetry and traits of leonthiasis. The tomographic images associated with renal osteodystrophy present trabecular bones with cortical expansion, which evidences the immature bone turnover present. Histopathology is not specific and may be similar to cases of craniofacial bone dysplasia. Given the above, it is essential to relate these findings to the clinic to define an adequate diagnosis.